Treatment of lower cervical spine fracture with ankylosing spondylitis by simple long anterior cervical plate: a retrospective study of 17 cases - Chen, Weifu; Yang, Yu; Pan, Wenjun; Lei, Xinhuan; Hong, Zhenghua; Luo, Hua (Frontiers in Neurology, 2024)
Objective Ankylosing spondylitis (AS), an autoimmune disease, often leads to lower cervical spine fractures, with the potential for severe spinal nerve damage even from low-energy injuries. The optimal treatment approach remains debated. Methods A retrospective study involved 17 AS patients with lower cervical spine fractures who received anterior cervical fixation. Most presented cervicothoracic or thoracolumbar kyphosis, with 11 exhibiting neurological deficits. Patient characteristics, clinical data, visual analog scale (VAS), complications, and nerve recovery were analyzed. Results No postoperative neurological deterioration occurred. All cases experienced complete fusion of fractures during the follow-up period. Preoperative VAS significantly decreased at 3 days and 3 months post-surgery. Of the 11 patients with preoperative neurological deficits, approximately 54.5% showed improvement post-surgery. No complications were reported, such as esophageal fistula, wound infection, or fixation failure. Conclusion Anterior internal fixation is a possible treatment for AS-related lower cervical fractures. This approach ensures satisfactory spinal stability and neurological recovery with proper cranial traction and external fixation post-surgery. Our findings demonstrate that this surgical method is safe and effective.